ANALISIS STRUKTUR JARINGAN KOMUNIKASI KELOMPOK WANITA PADA KEGIATAN USAHA TENUN MUNA DI DESA WAULAI KECAMATAN BARANGKA KABUPATEN MUNA BARAT - Sitti Musdalifah Nur; Awaluddin Hamzah; Ima Astuty Wunawarsih (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
This studies identifies the communication network structure of women's groups in Muna woven fabric business activities in Waulai Village, Barangka District, West Muna Regency. This study aims to: Determine how the structure of the communication network formed in the women's group in the Muna woven fabric business activity. This research was carried out in Waulai Village, Barangka District, West Muna Regency from November to December 2021. Sampling was carried out purposively on the weaving group, with respondents consisting of 5 groups totaling 50 people. Data collection was carried out by interviewing guided by the questionnaire and the data was processed using Microsoft Excel, analyzed using the communication network analysis method which was carried out using UCINET VI Software with a focus on the structure of the communication network, namely; Components, Clicks, Bridges, Hubs, Cutpoints, and Isolates. The results showed that: The structure of the communication network formed in the women's group in the Muna weaving business activity in Waulai Village, Barangka District, West Muna Regency, consisted of components, Kliks, Hubs, Bridges, Cutpoints, and Isolates. In the group communication network structure, it is necessary to increase communication activities for each individual so that no individual acts as an Isolate.